Accumulation of heavy metals (Zn, Cu, Pb, Cd) in flat-tree oysters Isognomon alatus exposed to pig farm effluent - Saed, Katayon; Ismail, Ahmad; Omar, Hishamuddin; Kusnan, Misri (Taylor and Francis, 2002)
Field experiments were conducted to measure the accumulation of heavy metals (Zn, Cu, Pb, Cd) in oysters Isognomon alatus transferred from the Sepang Kecil River (clean area) to the Sepang Besar River (polluted area), for a period of 6 months. Oysters were placed in an area near an effluent from pig farm. There were increase in all metals studied in the oysters introduced to the Sepang Besar River. The metals accumulated by transplanted oysters indicated chronic pollution by metals from the pig farm effluent. A significant difference was found between the accumulation rate of Zn and accumulation rates of the Cu, Pb and Cd. Accumulation rates of metals by oysters under field conditions were found to be 42.70, 1.77, 0.95 and 0.84 μg g-1 month-1 for Zn, Cu, Pb and Cd, respectively. It was also found that oysters have abilities to regulate their internal concentrations of metals over a range of external metal concentrations.